Clonal Selection Algorithm Based Iterative Learning Control with Random Disturbance - Qun Gu; Xiao Hong Hao; Xian Jun Du; Wei Tao Xu; Yuanyuan Ju (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Clonal selection algorithm is improved and proposed as a method to solve optimization problems in iterative learning control. And a clonal selection algorithm based optimal iterative learning control algorithm with random disturbance is proposed. In the algorithm, at the same time, the size of the search space is decreased and the convergence speed of the algorithm is increased. In addition a model modifying device is used in the algorithm to cope with the uncertainty in the plant model. In addition a model is used in the algorithm cope with the uncertainty in the plant model. Simulations show that the convergence speed is satisfactory regardless of whether or not the plant model is precise nonlinear plants. The simulation test verify the controlled system with random disturbance can reached to stability by using improved iterative learning control law but not the traditional control law. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1921